Magnetic Resonance Imaging of Metal on Metal Implants: A Breakthrough - Pilania, K; Jankharia, B (Nepalese Journal of Radiology, 2014)
Background: Metal-on-metal (MoM) hip replacement, a durable alternative to conventional metal -on-polyethylene hip replacement, is increasingly common nowadays. There is a 4-8% incidence of pain and complications which usually go undetected on radiographs. MRI has a vast potential for early diagnosis in these cases. Aim: To evaluate the feasibility of MR imaging in MoM hips and to review the MR imaging features of various complications associated with metal on metal hip implants. Materials and Methods: 41 patients with 52 replaced hips using MoM prostheses underwent MRI on a 1.5T scanner using standard clinical protocols optimized to minimize metallic susceptibility artifact, known as metal artefact reduction sequences (MARS). A standardized reporting was done with specific comment on periprosthetic osteolysis, loosening, periprosthetic soft tissue mass, gluteal muscle atrophy, iliopsoas atrophy, muscle edema, muscle/ tendon tear and lymphadenopathy. Results: Diagnostic images were obtained in all patients. Of the 52 hips, 32 had total hip replacement (THR) and 20 had resurfacing. The following abnormalities were found. Periprosthetic osteolysis (5), Periprosthetic soft tissue mass (24), Gluteal muscle atrophy – moderate to severe (15), Iliopsoas atrophy (15), Muscle edema (0), Muscle / tendon tear (0), Lymphadenopathy (5). Conclusion: MRI on a 1.5T scanner is a viable technique to image the MoM hip and shows well the various complications associated with post arthroplasty hips. DOI: http://dx.doi.org/10.3126/njr.v3i2.9607 Nepalese Journal of Radiology Vol.3(2)July-Dec, 2013: 49-56